Mobilizing Public and Private Funds for Inclusive Green Growth Investment in Developing Countries : A Stocktaking Report Prepared for the G20 Development Working Group - International Finance Corporation (International Finance Corporation, Washington, D.C., 2017)
The G20 countries have increasingly recognized the importance of green growth in recent years, and many countries are demonstrating strong leadership through effective and progressive policies.The focus has so far been on creating new economic opportunities while solving environmental and resource scarcity challenges. However, governments do not act alone—the private sector is a natural partner, providing new technologies, business models and investment opportunities across a variety of sectors to help scale-up transformation. Since the 2008 Pittsburgh G20 Summit, inorder to foster these partnerships and leadership by the private sector there has beena surge in related intergovernmental, non-governmental and private sector platforms, to actively promote government policies and public-private partnerships to deliver greater investment in resource-efficient, low-carbon infrastructure and services. As the largest development finance institution dedicated to private sector development,with a strong emphasis on sustainability,International Finance Corporation (IFC) was commissioned to undertake an extensive literature review as a stocktaking exercise on existingmechanisms to mobilize private capital for inclusive green growth (IGG) investmentsin developing countries, as preparation for LosCabos. This overview starts with the high-level findings of the expanded literature review. In order to help readers navigate the vast amounts of information reviewed, a software tool has been developed that allows searches by theme, geography, sector, instrument, and nother interests. The overview then provides a mapping of financial flows relevant to IGG based on existing information and identifies gaps in our knowledge along sectoral and geographical lines.